Identification and Interpretation of Spinal Cord Injuries in Robbery Victims: A Forensic Review - Kusumaningrat, Donald Rinaldi; Wahjoepramono, Eka Julianta; Purnamasari, Dewi (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Robbery is intrinsically a violent crime and is defined as the original criminal plan of the perpetrator by committing robbery, by force committed on occasion or with the pretext of robbery. Strangulation by ligature occurs when an external force is applied to the neck causing various traumatic pathologies. If the injury is severe enough, cerebral perfusion and oxygen delivery are compromised and can lead to asphyxia and rapid neuronal death. These injuries can be encountered in a variety of clinical scenarios and may be present in suicide attempts, sports injuries, motor vehicle trauma, and may have implications in the fields of criminology and forensic pathology. In this case, a 66-year-old woman who was a victim of a robbery suffered a neck injury. After examination, there was a fracture in the cervical spine and was diagnosed with spinal cord trauma. As a result of this injury, the victim suffered permanent paralysis. The perpetrators of the robbery are threatened with criminal penalties under 364 KUHP and/or Article 351 No 3 KUHP.